FOREIGN INVESTMENT AND GLOBAL NEGOTIATIONS: EMERGING ISSUES (NATIONAL CAPITAL LAW JOURNAL, 1997)
NA
Keywords: Foreign Direct Investment (FDI); Global Trade Negotiations; World Trade Organization (WTO); Trade-Related Investment Measures (TRIMs); Transnational Corporations (TNCs); Investment Liberalization; Multilateral Investment Framework; International Trade; Developing Countries; Investment Protection.